Аналіз можливостей створення ігрового контенту за допомогою Unreal Engine 5 - Козловець, С. О.; Рижкова, Є. М.; Боюка, М. Є.; Олещенко, В. Б. (ХНУРЕ, 2023)
During the work, a game was created using Unreal Engine 5. A practical comparison of various game engines was conducted and the most relevant was selected. The main stages of game development, such as planning, production, and testing of the finished product, have been worked out. Work has been carried out on the relevance of games in our time.
Keywords: Unreal Engine 5; ігровий контент